Communicable Diseases Surveillance: CDI volume 25 issue 2 (2001) - No author listed (Communicable Diseases Intelligence, 2001)
Communicable diseases surveillance highlights for 1st quarter, 2001 (bloodborne diseases, gastrointestinal disease, quarantinable diseases, sexually transmitted infections, vaccine preventable diseases, vectorborne diseases, zoonoses, other diseases, LabVISE), and surveillance outcomes from several reporting series as follows: Presentation of National Notifiable Diseases Surveillance System data; Corrections for CDI (Victorian Legionella commentary correction, non-TB mycobacteria, New South Wales National Notifiable Diseases Surveillance System tables correction); National Notifiable Diseases Surveillance System tables, 1 January to 31 March 2001; Laboratory Serology and Virology Reporting Scheme tables, 1 January to 31 March 2001; Australian Sentinel Practice Research Network report tables, weeks 1-4 to 9-12, 2001; Gonococcal surveillance, reporting period 1 July to 30 September 2000; Rotavirus surveillance, reporting period June 2000 to April 2001; HIV and AIDS surveillance, reporting period 1 October to 31 December 2000, assessed as at 31 March 2001; Australian childhood immunisation coverage, 1 October to 31 December 2000 cohort, assessed as at 31 March 2001.